Management of Lateral Multiple-Level Metastasis in N1b Papillary Thyroid Microcarcinoma - Wenlong Wang; Wenlong Wang; Zhejia Zhang; Yunzhe Zhao; Wenbo Xue; Fadao Xia; Xinying Li; Xinying Li (Frontiers in Oncology, 2020)
Background: The optimal extent of therapeutic lateral neck dissection (LND) in the management of N1b papillary thyroid microcarcinoma (PTMC) is still under debate in clinical practice. In this light, our study aims to explore the incidence, patterns, and predictive factors of the lateral multiple-level metastasis in N1b PTMC patients.Methods: The clinical records of 142 patients diagnosed with N1b PTMC who underwent therapeutic LND from July 2015 to November 2018 at our institution were retrospectively reviewed. Univariate and multivariate analyses were conducted to examine the predictive factors associated with lateral multiple-level metastasis. The recurrence-free survival was analyzed and confirmed by Kaplan–Meier plots and log-rank test.Results: The overall frequency of lateral multiple-level metastasis was 50.7% in N1b PTMC patients, and two-level to four-level simultaneous metastasis were present in 26.8, 17.6, and 6.3% patients, respectively. Extrathyroidal extension (ETE) (OR = 5.79, 95% CI, 1.36–24.59; P = 0.017) and the central metastatic lymph node ratio (CLNR) with values equal or higher than 0.61 (OR = 6.18, 95% CI, 2.53–15.09; P < 0.001) served as independent predictors of multiple-level metastasis in N1b PTMC patients. Moreover, locoregional recurrence was significantly higher in the selective neck dissection (SND) group compared to the modified radical neck dissection (MRND) one (HR = 3.65, 95% CI, 1.11–12.00; P = 0.03).Conclusion: Our results show that the lateral multiple-level metastasis was relatively common, and we suggest MRND to be considered for N1b PTMC patients with ETE or CLNR equal or higher than 0.61.